1994
DOI: 10.1002/mde.4090150407
|View full text |Cite
|
Sign up to set email alerts
|

Firm performance and board composition: Some new evidence

Abstract: HASH(0x1009eb8e0)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
3
6

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(95 citation statements)
references
References 30 publications
8
73
3
6
Order By: Relevance
“…The overall results, however, are consistent with the findings of earlier studies which have found no significant relationship between board composition and company performance (Rechner & Dalton, 1986;Fosberg, 1989;Daily & Dalton, 1993;Barnhart et al, 1994;Grace, Ireland & Dunstan, 1995;Dalton et al, 1998;Cho & Kim, 2007;Finegold et al, 2007). Despite the fact that studies by Fama and Jensen (1983), Baysinger and Butler (1985) and Baysinger and Hoskinsson (1990) have asserted that the effectiveness of a board depends on an optimal mix of executive and non-executive directors, the historical dearth of theory on the determinants of an optimal board composition (Hermalin & Weisbach, 2003) is also consonant with these findings.…”
Section: Results Of Hypothesis Testing H 1 : Board Composition (The Psupporting
confidence: 91%
See 1 more Smart Citation
“…The overall results, however, are consistent with the findings of earlier studies which have found no significant relationship between board composition and company performance (Rechner & Dalton, 1986;Fosberg, 1989;Daily & Dalton, 1993;Barnhart et al, 1994;Grace, Ireland & Dunstan, 1995;Dalton et al, 1998;Cho & Kim, 2007;Finegold et al, 2007). Despite the fact that studies by Fama and Jensen (1983), Baysinger and Butler (1985) and Baysinger and Hoskinsson (1990) have asserted that the effectiveness of a board depends on an optimal mix of executive and non-executive directors, the historical dearth of theory on the determinants of an optimal board composition (Hermalin & Weisbach, 2003) is also consonant with these findings.…”
Section: Results Of Hypothesis Testing H 1 : Board Composition (The Psupporting
confidence: 91%
“…Such measures may not bear any relationship to asset valuations, current operations or even the firm's historical profitability (Muth & Donaldson, 1998). Measures in this category include market-to-book ratio, Tobin's Q (Barnhart, Marr & Rosenstein, 1994) or constructed indices such as the Sharpe measure (Hoskisson, Johnson & Moesel, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…The mean proportion of outside Board directors is 65.64% which is similar to the 60.09% mean value registered in the US market by Barnhart et al (1994). The ownership structure clearly differs from those recorded in studies conducted in Anglo-Saxon economies.…”
Section: Sample and Databasesupporting
confidence: 49%
“…In addition Bernhart et al (1994), using both OLS and instrumental variables, find a curvilinear relationship between board structure and performance. In contrast, Klein (1998) …”
Section: Outside Directorsmentioning
confidence: 96%